Bacterial and protozoal agents of canine vector-borne diseases in the blood of domestic and stray dogs from southern Portugal - Carla Maia; Bruno Almeida; Mónica Coimbra; Maria Catarina Fernandes; José Manuel Cristóvão; Cláudia Ramos; Ângela Martins; Filipe Martinho; Pedro Silva; Nuno Neves; Mónica Nunes; Maria Luísa Vieira; et al. (Parasites & Vectors, 2015)
Abstract Background The so-called canine vector-borne diseases (CVBD) are caused by a wide range of pathogens transmitted by arthropods. In addition to their veterinary importance, many of these canine vector-borne pathogens can also affect the human population due to their zoonotic potential, a situation that requires a One Health approach. As the prevalence of vector-borne pathogens in cats from southern Portugal has been recently evaluated, the aim of the present study was to assess if the same agents were present in dogs living in the same area, and to assess positivity-associated risk factors. Methods One thousand and ten dogs (521 domestic and 489 stray) from veterinary medical centres and animal shelters in southern Portugal were enrolled. Anaplasma spp./Ehrlichia spp., Bartonella spp., Borrelia burgdorferi sensu lato, Babesia spp., Hepatozoon spp. and Leishmania infantum infections were evaluated by polymerase chain reaction (PCR) assays in blood samples. Results Sixty-eight (6.7%) dogs were PCR-positive to at least one of the tested CVBD agent species, genera or complex, including one dog found positive to two different genera. Nineteen (1.9%) dogs were positive to Anaplasma spp./Ehrlichia spp., eight (0.8%) to B. burgdorferi s.l., 31 (3.1%) to Hepatozoon spp. and 11 (1.1%) to L. infantum. Anaplasma platys, Ehrlichia canis, B. burgdorferis.l. and Hepatozoon canis were identified by DNA sequencing, including one animal confirmed with both A. platys and H. canis. Furthermore, Wolbachia spp. was amplified in blood from four dogs. None of the tested dogs was positive by PCR for Bartonella spp. or Babesia spp. Conclusions The molecular identification of CVBD agents in southern Portugal, some of them with zoonotic concern, reinforces the importance to alert the veterinary community, owners and public health authorities to prevent the risk of transmission of vector-borne pathogens among dogs and to other vertebrate hosts including humans. The prevalence of the selected pathogens was lower than that previously found in cats from the same region, probably because veterinarians and owners are more aware of them in the canine population and control measures are used more often.